Antenna Multiple Input Multiple Output Four Port Using Methods Stub and Defected Ground Structure for Ultra wide-band Applications - Denisa Putri Maharani; Yustini Yustini (International Journal of Wireless And Multimedia Communications, 2025)
Abstract— Multiple Input Multiple Output (MIMO) antennas using the Defected Ground Structure technique are able to produce wide bandwidth to meet Ultra Wide-Band (UWB) frequencies. UWB MIMO antennas have the advantages of reducing interference, improving isolation, and optimizing multipaths, thereby expanding coverage and improving signal quality. The challenge in designing MIMO-UWB antennas is to produce low mutual coupling with small antenna dimensions so that they can be used in portable devices. In this final project, the aim is to design a 4x4 UWB MIMO antenna using FR-4 substrate material with a dielectric constant (εr) of 4.3, a loss tangent of 0.035 and a material thickness of 1.6 mm. With dimensions of 45 x 45 x 1.6 ,mm-3. which has an Ultra-Wideband working frequency with a frequency range of 3.1 – 10.6 GHz. The results of the antenna simulation and measurement showed good performance with a simulated antenna operating frequency of 3.1–10.23 GHz, a minimum return loss of -49.85 dB, an isolation of ≤ -20 dB, and a maximum peak gain of 3.3 dBi at the frequency of 10.6 GHz with an omnidirectional radiation pattern. The measurement results show a working frequency of 3.2-10.64 GHz, a minimum return loss of -21.24 dB, and an Isolation of ≤ -20 dB. The designed four-port MIMO antenna parameters result in a simulated ECC and measurement < of 0.02 and a diversity gain of over 9.989, and a TARC of ≤ –10 dB. The measurement and simulation results show a good fit and are within the permissible limits, indicating good performance for UWB communication.